Comparative Efficacy of Closantel and Azadirachta indica against Strongyle Infection in Goats - Singh, Rajveer; Bagherwal, Rajendra K.; Mehta, Hemant K.; Choudhary, Nidhi S.; Jayraw, Anant K.; Awasthi, Shivam (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
This study was carried out to evaluate the comparative efficacy of closantel and Azadirachta indica seed powder against strongyle  infection in goats. Infected goats having >500 eggs per gram of faeces were included in the present study and divided into three groups  (A, B, and C) of six goats each. Group A animals were treated with closantel @ 10 mg/kg b.wt., Group-B with neem seed powder @ 4  g/kg b.wt, Group C with neem seed powder @ 8 g/kg b.wt. Number of eggs per gram of faeces (EPG) were recorded on day 0 (before  treatment), 7, 14, 21 and 28 day (post treatment). On the basis of EPG values, it was observed that closantel had more efficacy than  neem seed powder as percent reduction in EPG was higher in closantel treated goats (91.12%) as compared to neem seed powder @  8 g/kg body weight treated goats (62.49%). The efficacy of neem seed powder @ 4 g/kg b.wt was 38.09%. Thus, it was concluded that  higher dose of neem seed powder has effective against strongyle infection in goats.
Keywords: Anthelmintic efficacy; Goats; Neem seed; Strongyle